1985
DOI: 10.1159/000115791
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in Schizophrenic Disorders

Abstract: Regional cerebral blood flow was measured using a 133Xe inhalation technique in 16 schizophrenic patients and 20 healthy volunteers. The bilateral frontal blood flows in the patient groups were significantly lower than in the control group. In addition, the patient group having auditory hallucination showed a significantly increased blood flow predominantly in the left temporal region. On the other hand, the patient group without auditory hallucination showed a slightly increased flow in the right t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 11 publications
(16 reference statements)
5
12
0
Order By: Relevance
“…In a large number of PET or SPECT studies in schizo phrenics, it has been reported that hyperfunctional changes in the left temporal lobe arise during the psychot ic states with auditory hallucinations [10][11][12][13][14][15], although contrary findings, too, have been reported [16][17][18]. These studies support the present speculation that the hyperper fusion images in the left temporal lobe and amygdala may arise in association with the psychotic states.…”
Section: Discussionsupporting
confidence: 85%
“…In a large number of PET or SPECT studies in schizo phrenics, it has been reported that hyperfunctional changes in the left temporal lobe arise during the psychot ic states with auditory hallucinations [10][11][12][13][14][15], although contrary findings, too, have been reported [16][17][18]. These studies support the present speculation that the hyperper fusion images in the left temporal lobe and amygdala may arise in association with the psychotic states.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, left-sided coherence abnormalities did not become obvious when we analyzed EEGs recorded in the resting condition, also suggesting the clinical utility of this technique in the evaluation of brain dysfunction [8,26]. There have been electrophysiological and neuroimaging findings suggesting an association between positive symptoms and left-sided dysfunction in schizo-phrenia [40][41][42]. In fact, Norman et al [43] found that reality distortion symptoms (i.e., hallucinations and delusions) had a significant relationship with left fronto-temporal coherence abnormalities in their schizophrenic patients.…”
Section: Discussionsupporting
confidence: 49%
“…The relative hypoperfusion pattern in the frontal lobes is presumably compatible with so-called 'hypofrontality' phenomenon reported in studies with PET or Xe inhala tion techniques on medicated or unmedicated schizo phrenics [7][8][9][10], although this phenomenon was not found in schizophrenics in some other studies [11,12]. Further, slight relative hyperperfusion in the frontal lobes is known to be a more common phenomenon in normal subjects [13].…”
Section: Discussionsupporting
confidence: 69%